PROFITABILITAS DAN SOLVABILITAS PADA KINERJA KEUANGAN BANK SYARIAH - Wulan Martha Hayani; Aminar Sutra Dewi (Jurnal Ekonomi STIEP, 2023)
This study aims to examine the extent to which profitability and solvency ratios affect financial performance. This research is a quantitative research method using data in the form of financial statements of the Islamic banking sector at the Financial Services Authority for the period 2017 –2021. This study used a purposive sampling method. The results of the study show that the influence of the profitability ratio on the performance of the Islamic banking financial sector at the Financial Services Authority during the 2017 – 2021 period has no significant effect. Although the results in this study are not significant it does not mean that companies can ignore the Profitability ratio. Often conditions of high profit will be a consideration for investors in these companies in making investment decisions and creditors in loan decisions. Meanwhile, the solvency ratio of the Islamic banking sector at the Financial Services Authority during the 2017-2021 period as a whole is said to be in good condition and has a positive effect on financial performance. In this study, the data analysis method used was descriptive statisrics using the stata 14 program